Chitosan-alginate microcapsules of amoxicillin for gastric stability and mucoadhesion - Saahil Arora; R D Budhiraja (Wolters Kluwer Medknow Publications, 2012)
Amoxicillin-loaded microcapsules were prepared by ionotropic gelation of sodium alginate (ALG) with chitosan (CS) in presence of calcium chloride as gastroretentive delivery system. The effect of pH, concentration of ALG, CS and calcium chloride, and drug : ALG ratio were optimized in this study for minimizing the degradation of drug in acidic environment and increasing the loading efficacy and mucoadhesive efficiency of microcapsules. The optimum condition for prepared CS-ALG microcapsules was 2%w/v ALG, 0.75%w/v CS (pH5.0), and 1.0% w/v calcium chloride. The resulting microcapsules had drug entrapment efficiency of 84% and average size of 840 mm. CS concentration significantly influenced particle size and encapsulation efficiency of CS-ALG microcapsules (P<0.05). Decrease in the drug: ALG ratio resulted in an increased release of amoxicillin in acidic media. The relative decomposition of drug after encapsulation in CS-ALG microcapsules was decreased to 20.7%, 41.9%, and 83.3% in 2, 4, and 8 hours, respectively.